PENGGUNAAN SOTWARE GMT 6 DAN PYTHON UNTUK MENAMPILKAN PETA SEISMISITAS DAN MENGHITUNG BESAR SUDUT SUBDUKSI DIPULAU JAWA TAHUN 2021 - Maulina Putri Lestari; Budiarta, Budiarta; Perdana, Yusuf Hadi (Jurnal Stasiun Geofisika Sleman, 2023)
Mapping the seismicity of an area, especially in subduction areas which are prone to earthquakes such as Java, is needed in order to prove the existence of natural activities in the form of plate shifts and identify faults and lead people to be aware of possible disasters in the same area. In this context, research was carried out with the aim of making seismicity maps, cross sections, and focal mechanisms in the Java region using GMT 6 software and using the PYTHON programming language and script processing software in the form of ANACONDA. Then, area slices were made and subduction angles were calculated for each slice segment. The data used in this study is secondary data sourced from the BMKG and USGS with the data collection range from January to December 2021. The area taken is at coordinates 10.99° LS – 5.50° LS and 105.100° E – 115.145° E. Based on the analysis results obtained on the cross section map, there is evidence that in Java this is a plate subduction path marked by a decrease in the hypocenter of the earthquake. The mapped focal mechanism shows that the Java area is dominated by thrust faults. Earthquakes that occur very often are those with a small magnitude category, namely on a scale of 3-5 with a shallow depth of around 0-60 km. Plate shifts show that the steeper the plate, the older the subduction angle. The size of the angle according to BMKG data for 2021 for each slice segment is segment A-A' 75.7° – 80.1°, B-B' 80.8° – 82.7°, C-C' 69.8 ° – 75.2°, and D-D' 80.6° – 82.9°